Effect of Destination Image and Subjective Norm on The Intention to Visit Lombok Island Indonesia as The Best World Halal Tourism Destination - Sintesa Aulia Ramadhani; Mochamad Mochklas (Muhammadiyah International Journal of Economics and Business, 2019)
Lombok Island is one of the outstanding halal attractions in Indonesia. In fact, it is titled the Best Halal Travel Destination in Indonesia according to the IMTI 2018 and the best halal tourism destination at the international scale in the 2015 World Halal Travel Summit that was held at The Emirates Palace Ballroom, Abu Dhabi, United Arab Emirates (UAE). Moreover, Lombok Island won two awards at once, namely as the World’s Best Honeymoon Destination and the World’s Best Halal Tourism Destination. Besides being known as “the island of 1000 mosques,” Lombok is also well-known for its numerous accesses to buy halal food and to book Sharia hotels, as well as the provision of rules for visiting beaches and the presence of religious communities. Considering the achievements of Lombok Island, this study attempts to find out the features that attract tourists for visiting Lombok Island. Furthermore, the study aims to determine the effect of destination image and subjective norms on the intention to visit Lombok Island. As many as 100 respondents were involved with the criteria they were at least 17 years old and had never visited Lombok Island. Data analysis uses SPSS 22. The results of the study reveal that destination image and subjective norms have significant influence on the intention to visit halal tourism destination in Lombok Island.